Mình hướng dẫn cách làm còn lại bạn tự chạy cận và biến đổi nhé!
1/Đặtt=1+sin2x=>dt=2cosxsindx=sin2xdx
=>1=π/2∫0t3dt=14t4
2/ Ta có \frac{1}{cos^{4}x}=\frac{1}{cos^{2}x.cos^{2}x}=\frac{1}{cos^{2}x}.(1-tan^{2}x)
Thế vào sau đó đặt t=tanx=>dx=\frac{1}{cos^{2}x}dx
=>2=\int\limits_{0}^{\pi /4}(1-t^{2})dx=\int\limits dx-\int\limits t^{2}dx
3/ Đặt t=\sqrt{1+lnx}=>t^{2}=1+lnx=>dt=\frac{1}{x}dx
=>\int\limits tdt=\frac{1}{2}t^2
4/ \frac{1}{cosx}=\frac{cosx}{cos^{2}x}=\frac{cosx}{(1-sin^{2}x)} thế vào:
Đặt: t=sinx=>dt=cosxdx
=> 4=\int\limits\frac{1}{(1-t^{2})}dt=\frac{1}{(1-t)(1+t)}dt=-\frac{1}{2}ln\frac{|t-1|}{|t+1|}